Compact nanocrystalline silicon carbide high-hardness and high-toughness block material and preparation method thereof
The pretreated silicon carbide raw materials are processed through high-temperature and high-pressure sintering technology to control the microstructure of nanocrystalline silicon carbide blocks, and the problem of hardness and toughness of existing silicon carbide ceramic materials is solved, and nanocrystals with high hardness and high fracture toughness are achieved Silicon carbide block material.
Patent Information
- Application Number
- CN202411608171.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
Existing silicon carbide ceramic materials have challenges in improving hardness and fracture toughness, and it is difficult to take into account both high hardness and high toughness, limiting their application in industries requiring high mechanical properties.
The pretreated silicon carbide raw materials are processed through high-temperature and high-pressure sintering technology to control the grain size, stacking fault density and twin structure of the nanocrystalline silicon carbide block to improve its density, hardness and fracture toughness.
The high hardness and high fracture toughness of nanocrystalline silicon carbide blocks are achieved. Vickers hardness is equal to or higher than 30GPa, and the fracture toughness is equal to or higher than 4.5MPa·m1/2, which is suitable for tooling and precision processing fields.
Smart Images

Figure CN119462162A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic non-metallic materials, and in particular relates to a dense nanocrystalline silicon carbide block and a preparation method thereof. Background Art
[0002] Silicon carbide is a common structural ceramic material with good mechanical properties, excellent thermal stability and radiation resistance. However, commercial silicon carbide has limited hardness (~24.5GPa) and poor fracture toughness (~3.9MPa·m 0.5 ), these two points limit its wide application in industries that require high hardness and fracture toughness, such as cutting tools and abrasive materials. In order to improve the practicality of silicon carbide ceramics, its hardness and fracture toughness must be improved at the same time.
[0003] The inherent brittleness of silicon carbide makes it a major challenge to simultaneously enhance its hardness and fracture toughness. It is well known that material properties are closely related to their microstructure, so adjusting the microstructure of silicon carbide ceramics may be a key way to overcome this challenge. In recent years, through high temperature and high pressure technology, researchers have successfully prepared dense blocks of nanocrystalline cubic silicon carbide with an average grain size of only 10nm. Thanks to its unique microstructure, the Vickers hardness of this material has been significantly improved, reaching as high as 41.5GPa, comparable to single-crystalline cubic boron nitride. However, its fracture toughness is only 3.6MPa·m 1 / 2 This low toughness introduces greater risks and limitations in potential engineering applications. In addition, other research teams used rare earth oxides (RE2O3, where RE includes La, Nd, Y, and Yb) and alumina as sintering aids to prepare a fracture toughness of about 4.4 MPa·m at 40 MPa and 1800 °C. 1 / 2 However, due to the larger grain size (submicron level) inside the block and the lower hardness of the sintering aid, its Vickers hardness is only about 18.5 GPa.
[0004] Patent CN117383940A discloses a preparation method, which uses SiC micron powder (3-100μm), graphite powder, dispersant, binder and solvent as raw materials to synthesize high-strength and high-toughness silicon carbide ceramic materials. The material has a bending strength of 100-250MPa, a tensile strength of 50-100MPa, a compressive strength of 480-660MPa, and a fracture toughness of 3.8-4.2MPa·m 1 / 2, while the Vickers hardness is 20-28GPa. However, patent CN117383940A does not give a specific measurement method for its Vickers hardness, so it is impossible to determine whether it is an asymptotic hardness representing the actual hardness of the block material (for high-hardness materials, the measurement value obtained by the traditional single load measurement method cannot accurately reflect the actual hardness of the material). In addition, although the block material prepared under the CN117383940A patent exhibits higher hardness and fracture toughness, since the material is not composed of a single silicon carbide, there is a large amount of graphite, which will limit its application in high temperature environments.
[0005] Therefore, obtaining SiC bulk materials with both high hardness and high toughness remains a difficult challenge. Summary of the invention
[0006] In view of the various deficiencies of silicon carbide ceramic materials in the above-mentioned prior art, the industry is in great need of developing new dense silicon carbide crystal materials with high toughness and high hardness.
[0007] The present invention obtains a dense, high-toughness, high-hardness nanocrystalline silicon carbide bulk material by sintering various pre-treated silicon carbide raw materials at high temperature and high pressure. The inventor unexpectedly found that by controlling the grain size of the nanocrystalline silicon carbide bulk material within a relatively small range and forming more stacking faults and twin structures in the grains, the nanocrystalline silicon carbide bulk material can be ensured to have both high hardness and high toughness.
[0008] Therefore, the technical solution of the first aspect of the present application is a nanocrystalline silicon carbide block, the average grain size of which is less than 100 nm, the grains contain stacking faults and twin structures, and the stacking fault density is 1.1*10 12 / cm 2 Up to 1.4*10 12 / cm 2 The twin thickness is 3.2nm to 4.5nm; the volume of the bulk material is greater than 1mm 3 , relative density is greater than or equal to 98%. The asymptotic hardness value of the Vickers hardness of the block is equal to or higher than 30GPa, and the fracture toughness is equal to or higher than 4.5MPa·m 1 / 2 .
[0009] The technical solution of the second aspect of the present application is a method for preparing a nanocrystalline silicon carbide bulk material, the preparation method comprising the following steps:
[0010] A) Pretreatment: Weighing a mixed phase silicon carbide nanopowder composed of a cubic phase (3C) and a hexagonal phase (2H), and subjecting it to a heat treatment, wherein the grain size of the silicon carbide nanopowder is 10 to 100 nm, and the stacking fault density in the silicon carbide nanopowder grains is 1.4 to 2.5*10 12 / cm 2 , the average twin thickness is 1.2~2.8nm;
[0011] B) Pre-pressing: pre-pressing the heat-treated raw material to obtain a pre-pressed green body;
[0012] C) sintering: sintering the pre-pressed green body obtained in step B) at high temperature and high pressure;
[0013] D) Discharging: Cooling and depressurizing the high-temperature and high-pressure sintering equipment in step C), then taking out the sintered silicon carbide block, and performing optional post-treatment to obtain a dense nanocrystalline silicon carbide block with high hardness and high toughness.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] 1. The raw material used is a mixed phase of cubic and hexagonal phases. The silicon carbide grain size in the raw material is less than 100nm. In addition, the grains also contain a large number of lattice defects such as stacking faults and twins, which promote the densification of the sample.
[0016] 2. Compared with the sintering technology without pretreatment, the pretreatment technology proposed in the present invention can effectively remove organic matter in silicon carbide nanopowder and oxygen adsorbed on the surface.
[0017] 3. Different from various pressureless, hot pressing and spark plasma sintering technologies, the high temperature and high pressure technology requires a lower sintering temperature and does not require any sintering aids, and the grain boundary sintering of silicon carbide blocks is good.
[0018] 4. Different from the silicon carbide film obtained by chemical vapor deposition, the silicon carbide obtained by high temperature and high pressure sintering is a block material with thicker thickness and is more suitable for mechanical processing. In addition, the size of the sample can be further increased, and the actual application range is wider.
[0019] 5. In high temperature and high pressure sintering, high temperature can promote the merging of grains and the formation of strong interfaces, and high pressure can restrain atomic diffusion and limit grain coarsening, thereby improving the density and hardness of the sintered samples. The average grain size of the obtained silicon carbide sample is very small, with a minimum of about 30nm. And by adjusting the raw material precursor and sintering process, nanocrystalline silicon carbide toughness blocks with different microstructures can be obtained.
[0020] 6. The relative density of the block material is greater than or equal to 98%, close to complete density.
[0021] 7. The fracture toughness of silicon carbide samples obtained by indentation method combined with Anstis formula is equal to or higher than 4.5MPa·m 1 / 2 , up to 5.1MPa·m 1 / 2, is a nanocrystalline silicon carbide bulk material with high fracture toughness. In addition, the bulk material has excellent hardness, which is equal to or higher than 30GPa, and can reach up to 35GPa. This material can be made into cutting tools and has great application potential in the field of precision machining. Therefore, this research result is of great significance to expanding the application range of silicon carbide.
[0022] The nanocrystalline silicon carbide bulk material and the preparation method thereof of the present invention are further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 (A), (B), (C), (D), (E), and (F) respectively show optical photographs of samples obtained in Examples 1, 2, 3, 4, 5, and 6 of the present invention;
[0024] Figure 2 The X-ray diffraction diagram of the nanocrystalline silicon carbide bulk material obtained in Example 5 of the present invention is shown;
[0025] Figure 3 The scanning electron microscope image of the fracture surface of the nanocrystalline silicon carbide block obtained in Example 5 of the present invention is shown;
[0026] Figure 4 Scanning transmission electron microscope images of the nanocrystalline silicon carbide bulk material obtained in Example 5 of the present invention are shown, (A) is a scanning transmission bright field image of the crack extension characteristics of the sintered sample; (B) is an enlarged view of the red frame area in (A); (C) and (D) are high-angle annular dark field images of the middle and tip areas of the crack extension of the sintered sample, the red line and yellow arrows represent the twin boundary (TB) and stacking fault (SF), respectively, and the position of the grain boundary (GB) is marked.
[0027] Figure 5 The hardness-load curve of the nanocrystalline silicon carbide bulk material obtained in Example 5 of the present invention is shown, and the small figure in the upper right corner is an optical picture of the Vickers indentation of the bulk material under a load of 0.7 kg. DETAILED DESCRIPTION
[0028] The technical solution of the first aspect of the present application is a nanocrystalline silicon carbide block, the average grain size of which is less than 100 nm, and the grains contain stacking faults and twin structures, wherein the stacking fault density is 1.1*10 12 / cm 2 Up to 1.4*10 12 / cm 2 The twin thickness is 3.2nm to 4.5nm; the volume of the bulk material is greater than 1mm 3, relative density (density) is greater than or equal to 98%. According to the measurement, the asymptotic hardness value of the Vickers hardness of the block is equal to or greater than 30GPa, and the fracture toughness is equal to or greater than 4.5MPa·m 1 / 2 .
[0029] In this application, unless otherwise specified or defined, all terms should be interpreted as having the meanings as commonly understood by those skilled in the art.
[0030] In the context of the present application, "nanocrystalline silicon carbide" refers to a material that is substantially composed of silicon carbide in terms of chemical composition, and that is composed of numerous silicon carbide grains having a size in the nanometer range in terms of microstructure.
[0031] In the context of this application, "relative density" (or "density") is a dimensionless value that measures the sintering condition of a bulk material. The relative density is obtained by dividing the actual density measured by the Archimedean method by the theoretical density of silicon carbide. The closer the relative density is to 100%, the denser the bulk material.
[0032] In the context of this application, "Vickers hardness" refers to the hardness of a material measured by the indentation method, that is, by applying a certain load to press the indenter (usually a diamond indenter) into the sample being tested, leaving a mark of plastic deformation on the sample surface after the load is removed, and then dividing the applied load by the area of the indentation to obtain the Vickers hardness of the sample. When measuring the Vickers hardness, a diamond right pyramid indenter with an angle of 136° between the relative faces is used to press vertically into the material surface under a certain pressure and hold for a certain period of time, leaving a diamond indentation caused by plastic deformation on the sample surface; the area of the indentation is calculated by measuring the diagonal length of the indentation left after unloading. Specifically, the calculation formula for Vickers hardness is: H v =1854.4F / L 2 , where F is the load size, in N; L is the average diagonal length of the indentation, in μm. It is worth noting that since the hardness value of the material varies within a certain pressure load range, especially for superhard materials, the material has a high stiffness and the elastic strain of the indentation under a small load is large, resulting in a high hardness measurement value. Only when the load is greater than a certain limit value, the material hardness tends to a constant value, that is, the asymptotic hardness value. For the nanocrystalline silicon carbide block material of the present application, all Vickers hardnesses are the true hardness values of the material obtained by variable load measurement, that is, the hardness of the material is measured by a variable load method, and the hardness value in the hardness-load curve where the hardness value remains unchanged with the load (i.e., the asymptotic hardness value) is taken as the final measurement value.
[0033] Those skilled in the art understand that the fracture toughness of a material refers to its ability to resist crack propagation. There are many ways to measure the fracture toughness of a material, and the values obtained by different methods cannot be simply compared. In the context of this application, "fracture toughness" refers to the ability of a material to resist crack propagation measured by indentation, which is obtained by the following formula: K Ic =0.016(E / H V ) 0.5 F / C 1.5 E is the Young's modulus of the bulk material, H V is the Vickers hardness of the indentation, F is the load used, and C is the average fracture length of the crack.
[0034] Those skilled in the art understand that there are a variety of technical means to obtain the microstructural information of the material. For example, direct observation can be performed using instruments such as a scanning electron microscope or a transmission electron microscope, or analysis can be performed using an X-ray spectrum. For accurate characterization, it is preferred to analyze samples inside the material; in addition, in order to avoid interference from a small amount of contaminants that may be present in the sample, multiple (for example, more than 3 or more than 5) sample points can be randomly taken for analysis. The stacking fault density (indicates the number of stacking faults present per unit area) and the thickness of the twin can be characterized and measured by a transmission electron microscope.
[0035] Those skilled in the art will appreciate that the nanocrystalline silicon carbide block material of the present application is substantially composed of pure silicon carbide, but does not exclude the inevitable small amount of impurities present in the raw material itself or introduced unintentionally during the processing and manufacturing process. For the purpose of the present invention, the weight content of impurities in the nanocrystalline silicon carbide material of the present application is usually at most 1%, preferably less than 0.5%, more preferably less than 0.3%, for example less than 0.2%, less than 0.1%, less than 0.05%.
[0036] The grain size of the silicon carbide grains in the nanocrystalline silicon carbide bulk material of the present application is generally between 1nm and 100nm, for example, the grain size can be greater than 2nm, greater than 3nm, greater than 4nm, greater than 5nm, greater than 8nm, greater than 10nm, greater than 20nm, greater than 30nm, or greater than 40nm, and the grain size can be less than 100nm, less than 90nm, less than 80nm, less than 70nm, less than 60nm, or less than 50nm. The grain size of silicon carbide can be measured by those skilled in the art based on transmission electron microscopy data.
[0037] In the grains of the nanocrystalline silicon carbide bulk material of the present application, the stacking fault density is generally 1.1*10 12 / cm 2 Up to 1.4*10 12 / cm 2 , for example, it can be about 1.1*1012 / cm 2 , 1.15*10 12 / cm 2 , 1.2*10 12 / cm 2 , 1.25*10 12 / cm 2 , 1.3*10 12 / cm 2 , 1.35*10 12 / cm 2 , 1.4*10 12 / cm 2 , or any density within any range consisting of any one of these densities as the upper or lower limit.
[0038] In the grains of the nanocrystalline silicon carbide bulk material of the present application, the twin thickness is generally 3.2nm to 4.5nm, for example, it can be 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4.0nm, 4.1nm, 4.2nm, 4.3nm, 4.4nm, 4.5nm, or any thickness within any range formed by any one of these thicknesses as the upper or lower limit.
[0039] The nanocrystalline silicon carbide of the present application is a bulk material, that is, it is used in the form of a bulk material. "Block material" in the present application is understood as an independent single material body, and there is no huge difference between the sizes of its three dimensions, so as to distinguish it from fibrous materials, thin sheets or film materials, and powder or granular materials. The nanocrystalline silicon carbide of the present application is a bulk material, and its volume is usually at least 1mm 3 , for example at least 2 mm 3 , at least 5mm 3 , at least 10mm 3 , at least 20mm 3 , at least 50mm 3 , at least 100mm 3 The upper limit of the volume of bulk materials is not particularly limited and can be selected according to actual needs and equipment processing capabilities. For example, it can be as high as 1000cm 3 .
[0040] The present application has no particular restrictions on the shape of the nanocrystalline silicon carbide block. According to actual needs, the block can be directly made by using a corresponding mold or processed by cutting and grinding into blocks of various shapes, such as cylindrical, prism, spherical, cuboid, etc. For example, the nanocrystalline silicon carbide block can be cylindrical with a diameter of 0.5 to 80 mm and a height of 0.5 to 50 mm.
[0041] The nanocrystalline silicon carbide block of the present application is very dense, has very excellent fracture toughness and good hardness, its relative density is above 98%, the Vickers hardness value is equal to or higher than 30GPa, and the fracture toughness is equal to or higher than 4.5MPa·m 1 / 2 .
[0042] It has been found that during the sintering process of silicon carbide, silicon carbide will produce lattice defects in situ under the action of shear force, including twins and stacking faults. Therefore, by carefully controlling the sintering conditions, the required stacking faults and twins can be formed in the nanocrystalline silicon carbide bulk. However, if the initial raw material that contains a large number of lattice defects such as twins and stacking faults is used to sinter the nanocrystalline silicon carbide bulk, then a considerable part of these lattice defects will be retained in the final product, which can greatly reduce the stringent requirements for sintering conditions, so that the high toughness, high hardness, and dense nanocrystalline silicon carbide bulk of the present application can be formed under conventional sintering conditions. Generally, the more lattice defects in the initial raw material, the more helpful it is to obtain a silicon carbide nanocrystalline bulk with a high density of lattice defects. Therefore, it is preferred to use a raw material that contains lattice defects such as twins and stacking faults to prepare the nanocrystalline silicon carbide bulk described in the first aspect of the present application.
[0043] Therefore, the second aspect of the present application provides a method for preparing the nanocrystalline silicon carbide bulk material according to the first aspect, the method comprising the following steps:
[0044] A) Pretreatment: Weigh a mixed phase silicon carbide nanopowder composed of a cubic phase (3C) and a hexagonal phase (2H), and subject it to a heat treatment (e.g., in a tube furnace), wherein the grain size of the silicon carbide nanopowder is 10 to 100 nm (it is a single-sized grain or a mixture of grains of several sizes, and may or may not be pickled), and the stacking fault density in the silicon carbide nanopowder grains is 1.4 to 2.5*10 12 / cm 2 , the average twin thickness is 1.2~2.8nm;
[0045] B) Pre-pressing: pre-pressing the heat-treated raw material to obtain a pre-pressed green body;
[0046] C) sintering: sintering the pre-pressed green body obtained in step B) at high temperature and high pressure;
[0047] D) Discharging: Cooling and depressurizing the high-temperature and high-pressure sintering equipment in step C), then taking out the sintered silicon carbide block, and performing optional post-treatment to obtain a dense nanocrystalline silicon carbide block with high hardness and high toughness.
[0048] The raw material used in step A) of the method is silicon carbide nanopowder, that is, silicon carbide powder with a nanometer grain size. Preferably, the grain size of the silicon carbide nanopowder used is 10 to 100 nm (for example, 10 nm, 12 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or any grain size within any numerical range formed with these sizes as endpoints), preferably 10 to 50 nm. The method can use silicon carbide nanopowder with a single grain size or a mixture of silicon carbide nanopowders with several different grain sizes. The frequency distribution of its grain size can be statistically analyzed by transmission electron microscopy, and the average grain size of the powder can be calculated based on the distribution diagram.
[0049] In the grains of the silicon carbide nanopowder used in step A) of the method, the stacking fault density is generally 1.4*10 12 / cm 2 Up to 2.5*10 12 / cm 2 , for example, it can be about 1.4*10 12 / cm 2 , 1.5*10 12 / cm 2 , 1.6*10 12 / cm 2 , 1.7*10 12 / cm 2 , 1.8*10 12 / cm 2 , 1.9*10 12 / cm 2 , 2.0*10 12 / cm 2 , 2.1*10 12 / cm 2 , 2.2*10 12 / cm 2 , 2.3*10 12 / cm 2 , 2.4*10 12 / cm 2 , 2.5*10 12 / cm 2 , or any density within any range formed by taking any of these densities as the upper or lower limit; for example, it can preferably be 1.7*10 12 / cm 2 Up to 2.1*10 12 / cm 2 .
[0050] In the grains of silicon carbide nanopowder used in step A) of the method, the twin thickness is generally 1.2 nm to 2.8 nm, for example, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, or any thickness within any range consisting of any of these thicknesses as the upper or lower limit; for example, preferably 1.5*10 12 / cm 2 Up to 1.9*10 12 / cm 2 .
[0051] The silicon carbide nanopowder used in step A) of the method can be the initial raw material or can be treated with hydrofluoric acid.
[0052] The various raw materials used in step A) of the process are preferably of high purity, for example, their purity is preferably higher than 99%, more preferably higher than 99.5%.
[0053] In terms of raw material selection, this application uses a mixed phase raw material of cubic phase (3C) and hexagonal phase (2H). The stacking fault density in the raw material is 1.4*10 12 / cm 2 Up to 2.5*10 12 / cm 2 (For example, it can be about 1.7 to 2.1*10 12 / cm 2 ), the average twin thickness is 1.2nm to 2.8nm (for example, it can be about 1.5 to 1.8nm). The inventor unexpectedly discovered that during the sintering process, stacking faults (SF) can serve as channels for atomic migration, because they provide space for sliding between atomic layers, allowing atoms to move more easily in the stacking fault area, which promotes the densification sintering of silicon carbide. Combined with the high surface energy brought by the small size of the raw material itself, this kind of raw material can be easily sintered into a block.
[0054] In step A) of the method, the silicon carbide nanopowder is heat treated by a tube furnace or other device. In a preferred embodiment of the present invention, the pretreatment is carried out at a temperature of 500°C to 1500°C in a vacuum or with a protective gas (nitrogen, argon, etc.), with a heating rate of 5 to 20°C / min and a holding time of 10 to 30min, so as to obtain a green body with less impurities and adsorbed gas. The treatment temperature can be, for example, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, etc., or any temperature within any range consisting of any of these temperatures as the upper or lower limit.
[0055] In step B) of the method, the raw material is pre-pressed. Cold pressing can be performed on a conventional green compacting machine or a hydraulic press, usually at room temperature, in air or in an inert atmosphere. The pre-pressing pressure in step 2 of the present invention is not particularly limited, as long as the green compact is ensured to be dense.
[0056] In step C) of the method, the pre-pressed green body obtained in step B) is subjected to high temperature and high pressure sintering. The order of pressurization and heating for high temperature and high pressure sintering is not fixed. It can be first pressurized to the highest pressure and then heated, or it can be pressurized to an intermediate pressure and then heated, then pressurized to the highest pressure with temperature, and finally heated to the highest temperature. In a preferred embodiment of the present invention, sintering is carried out under pressure conditions of more than 8GPa and less than 28GPa, and temperature conditions of more than 1000℃ and less than 2500℃, and the holding time is 1 to 60min to obtain silicon carbide ceramics with high hardness. The sintering pressure is, for example, 8 GPa, 9 GPa, 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa, 15 Pa, 16 GPa, 17 GPa, 18 GPa, 19 GPa, 20 GPa, 21 GPa, 22 GPa, 23 GPa, 24 GPa, 25 GPa, 26 GPa, 27 GPa, 28 GPa, etc., or any pressure within any range consisting of any of these pressures as the upper or lower limit. Generally, a higher sintering pressure is beneficial to improving the hardness of the sintered sample, so the sintering pressure is preferably 10 to 28 GPa. The sintering temperature may be, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, or any temperature within any range consisting of any of these temperatures as the upper or lower limit. In step C), the preferred holding time is 1 to 60 min, such as 5 to 45 min or 5 to 30 min. The heating rate in step C) may be controlled between 50 and 150°C / min.
[0057] The sintering process can be carried out using a high temperature and high pressure sintering device well known to those skilled in the art, such as a T25 press produced by Rockland Research, Inc., USA. The sintering process can be carried out in an inert atmosphere or in air as required. The sintering is single-phase sintering without adding any sintering aid.
[0058] After sintering is completed, the sintered sample is cooled and depressurized in step D). After depressurization is completed, the sintered sample is taken out, and after optional processing and post-processing (such as grinding and polishing, etc.), the nanocrystalline silicon carbide toughness block of the present application is obtained. The cooling in step D) can be natural cooling or controlled cooling, for example, the cooling rate can be 50 to 150°C / min, or it can be emergency stop cooling.
[0059] The experiment found that nanoscale grains, close intercrystalline bonding, and stacking faults in bulk materials (density of about 1.1*10 12 / cm 2 Up to 1.4*10 12 / cm 2 ) and twin structure (about 3.2nm~4.5nm) result in the block material having both high hardness and high toughness. It was also observed that the higher the density of stacking faults, the smaller the twin thickness, and the higher the density, the higher the fracture toughness of the sample. When the sample is sintered densely, the smaller the grain size, the higher the Vickers hardness of the sample. The inventor believes that the hardness of the silicon carbide block can be further improved by closely bonding small-sized nanograins, so that the advantages of fine grain strengthening of the block material can be reflected, so that the hardness of the final sample can exceed 30GPa; at the same time, on the other hand, the lattice defects derived from the initial raw materials and some in-situ formation can achieve the improvement of the fracture toughness of silicon carbide by dissipating energy and extending the crack propagation path. Specifically, like diamond, the twin structure in silicon carbide can temporarily prevent crack propagation and cause it to shift to the adjacent twin domain; the stacking faults and twins at the crack tip can also serve as channels for crack propagation, thereby producing a microcrack toughening effect; in addition, regardless of the crack location, its propagation is mainly along the (111) plane, and the twins and stacking faults on this plane play a role in extending the crack propagation path.
[0060] The present invention obtains nanocrystalline silicon carbide toughness blocks using silicon carbide nanopowder as raw material by optimizing high temperature and high pressure sintering conditions. The densification of the block, good interface bonding between grains, and internal stacking faults are the prerequisites for nanocrystalline silicon carbide blocks to have better toughness. The present invention unexpectedly discovered that by adjusting the raw material size, improving the pretreatment process, and adjusting the sintering parameters (pressure, temperature, holding time, etc.), a mixed phase raw material of cubic phase and hexagonal phase with high stacking fault density can be used to obtain nanocrystalline silicon carbide blocks with both good hardness and excellent toughness. In contrast, the silicon carbide blocks provided by the prior art are often difficult to balance high hardness and high toughness. For example, the method disclosed in Chinese Patent ZL 202111574952.0 uses hydrofluoric acid-treated silicon carbide nanopowder as a precursor to sinter superhard blocks by high temperature and high pressure method. Although the Vickers hardness of the block provided by the patent reaches the superhard level, which can be as high as 41.5GPa, its fracture toughness has been tested to be only about 3.6MPa·m 1 / 2 , which is significantly lower than the fracture toughness data of the bulk material in this application.
[0061] The nanocrystalline silicon carbide bulk material and preparation method of the present application are further described below in conjunction with embodiments.
[0062] Example
[0063] The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents a specific embodiment of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without departing from the principles of the present invention and without making creative work are within the scope of protection of the present invention.
[0064] For the sake of simplicity, some materials, equipment and method steps commonly used in the art are not specified in the examples. All process methods and analytical test processes (and related parameters) not specifically specified in the examples are carried out according to those commonly used by those skilled in the art; materials and equipment without specific sources are conventional laboratory materials and equipment.
[0065] Raw materials, equipment and material analysis and testing methods
[0066] The high temperature and high pressure sintering device used in each embodiment is a T25 press produced by Rockland Research, Inc., USA. The silicon carbide powder raw materials used in each embodiment are provided by GetNanoMaterial, Innochem and Alfa Aesar. The specific raw materials and related parameters are shown in the table below.
[0067]
[0068] The main analysis and detection methods and instruments used in each embodiment are as follows:
[0069] X-ray diffraction: Rigaku DMAX-2500 / P was used to measure the XRD spectrum. The scanning speed was 2 degrees per minute and the range was 20 degrees to 90 degrees.
[0070] SEM: Thermo Fisher Scios DualBeam was used for sample fracture analysis. The voltage was 5KV and the current was 0.1nA.
[0071] TEM: TEM samples (5 × 10 × 0.06 μm) were prepared by focused ion beam (FIB) and tested by a Thermo Fisher Talos F200X scanning transmission electron microscope and a JEM-ARM300 F2 from JEOL, with accelerating voltages of 200 kV and 300 kV, respectively.
[0072] Average grain size measurement method: The frequency distribution of grain sizes of raw materials and bulk materials can be statistically analyzed by transmission electron microscopy, and the average grain size of the powder can be calculated based on the frequency distribution diagram.
[0073] Measurement method of stacking fault density and twin thickness: The stacking fault density and twin thickness are characterized and measured by transmission electron microscopy. The stacking fault density is the number of stacking faults per unit area on the silicon carbide particles / silicon carbide grains, and the twin thickness is the distance between two adjacent twin boundaries. In order to obtain accurate data, we conducted a detailed transmission electron microscopy analysis on 100 silicon carbide particles / grains, took high-resolution images, counted the number of stacking faults and twin thickness, and calculated the stacking fault density and the average thickness of the twins based on the results.
[0074] Vickers hardness and fracture toughness test method: Use the German KB-30-S microhardness tester to test the Vickers hardness of the sample, and the test parameters are loading for 10s and holding pressure for 15s. That is, use a diamond regular pyramid indenter with an angle of 136° between the relative faces to press vertically into the material surface under a certain pressure and maintain it for a certain time (loading time is 10s, holding time is 15s), leaving a diamond indentation caused by plastic deformation on the sample surface, and then divide the applied load by the area of the indentation to get the hardness measured by the indentation method. The calculation formula for Vickers hardness is: H v =1854.4F / L 2 , where F is the load applied, in N; L is the average diagonal length of the indentation, in μm. The hardness measurement is carried out using a variable load method, and the hardness value of the sample in the area where the load remains constant (i.e., the asymptotic hardness value) is taken as the final hardness measurement value, such as Figure 5 The fracture toughness of the block is tested by the indentation method, and the calculation formula is: KIc =0.016(E / H V ) 0.5 F / C 1.5 E is the Young's modulus of the bulk material, H V is the Vickers hardness obtained by using the indentation, F is the load used, and C is the average fracture length of the crack. The optical image of the Vickers indentation with cracks produced by the sample under a load of 0.7Kg is shown in Figure 5 The crack length can be measured from the optical photograph.
[0075] Example 1
[0076] 0.3g of nanocrystalline silicon carbide initial raw material (GetNanoMaterials SiC-100) was vacuum heat treated in a tube furnace. The heating rate was 5℃ / min, the maximum temperature was 500℃, and the holding time was 30min. The treated powder was cold pressed into a column and placed in an assembly block, and then the assembly block was loaded into a T25 press and sintered at a pressure of 8GPa and a temperature of 1700℃. The sintered silicon carbide block is as follows Figure 1 (A) is shown. The central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a mixed phase of cubic and hexagonal phases. Its relative density, Vickers hardness, and fracture toughness are shown in Table 1, and its grain size, stacking fault density, and twin thickness measurements are shown in Table 2.
[0077] Example 2
[0078] A tubular furnace was used to heat treat 0.3 g of silicon carbide raw material (GetNanoMaterials SiC-101) after hydrofluoric acid pickling. The whole process was carried out in a nitrogen environment. The heating rate was 10°C / min, the maximum temperature was 1000°C, and the holding time was 20 minutes. The treated powder was cold pressed into a column and placed in an assembly block, and then the assembly block was loaded into a T25 press and sintered at a pressure of 15GPa and a temperature of 1500°C for 5 minutes. The heating rate was 50°C / min, and the cooling rate was 50°C / min. The sintered silicon carbide block is as follows Figure 1 As shown in (B), the central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a mixed phase of cubic phase and 2H. Its relative density, Vickers hardness and fracture toughness are shown in Table 1, and its grain size, stacking fault density and twin thickness measurement values are shown in Table 2.
[0079] Example 3
[0080] Mix 0.15g of silicon carbide raw material with an average grain size of 10nm (mixed-phase silicon carbide, GetNanoMaterials SiC-100) and 0.15g of silicon carbide raw material with an average grain size of 70nm (cubic phase silicon carbide, Alfa Aesar44646). Use a tubular furnace to heat treat the mixed raw materials, and the whole process is carried out in an argon environment. The heating rate is 10℃ / min, the maximum temperature is 1000℃, and the holding time is 20min. The treated powder is cold pressed into a column and placed in an assembly block, and then the assembly block is loaded into a T25 press and sintered at a pressure of 20GPa and a temperature of 1500℃ for 5min. The heating rate is 150℃ / min, and the cooling rate is 150℃ / min. The sintered silicon carbide block is as follows Figure 1 As shown in (C), the central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a mixed phase of cubic and hexagonal phases. Its relative density, Vickers hardness, and fracture toughness are shown in Table 1, and its grain size, stacking fault density, and twin thickness measurement values are shown in Table 2.
[0081] Example 4
[0082] 0.3g of silicon carbide raw material (GetNanoMaterials SiC-101) pickled with hydrofluoric acid was vacuum heat treated in a tubular furnace. The heating rate was 20℃ / min, the maximum temperature was 1500℃, and the holding time was 5min. The treated powder was cold pressed into a column and placed in an assembly block, and then the assembly block was loaded into a T25 press and sintered at a pressure of 25GPa and a temperature of 1400℃ for 5min. The heating rate was 50℃ / min and the cooling rate was 50℃ / min. The sintered silicon carbide block is as follows Figure 1 As shown in (D), the central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a mixed phase of cubic and hexagonal phases. Its relative density, Vickers hardness and fracture toughness are shown in Table 1, and its grain size, stacking fault density and twin thickness measurement values are shown in Table 2.
[0083] Example 5
[0084] Use a tubular furnace to vacuum heat treat 0.3g of silicon carbide raw material (GetNanoMaterials SiC-101) after hydrofluoric acid pickling. The heating rate is 20℃ / min, the maximum temperature is 1500℃, and the holding time is 5min. The treated powder is cold pressed into a column and placed in an assembly block, and then the assembly block is loaded into a T25 press and sintered at a pressure of 25GPa and a temperature of 1500℃ for 5min. The heating rate is 50℃ / min, and the cooling rate is 50℃ / min. The heating rate is 50℃ / min, and the cooling rate is 50℃ / min. The sintered silicon carbide block is as follows Figure 1 (E), the central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a single cubic phase silicon carbide, and its relative density, Vickers hardness, and fracture toughness are shown in Table 1. Its grain size, stacking fault density, and twin thickness measurements are shown in Table 2.
[0085] The X-ray diffraction image of the sample in Example 5 is as follows: Figure 2 The fracture scanning electron microscope images and transmission electron microscope (including high resolution) images are shown in Figure 3 and Figure 4 The hardness-load curve is shown in Figure 5 shown. Figure 2 It was demonstrated that the bulk material consists of a single cubic phase of silicon carbide. Figure 3 It proves that it has been sintered very densely. Figure 4 (A) reflects that the grain size of the sample is very small. Figure 4 In (A) and 4(B), the microstructure of the crack propagation region in the sintered samples mainly shows transgranular fracture. Figure 4 In (C) and 4(D), two magnified HAADF-STEM images of selected areas along the crack are shown. It is worth noting that the twin boundaries within the nanograins temporarily stop the crack and deviate the crack from the adjacent twin domain. The crack propagates along the (111) plane in the silicon carbide grains, and both twins and stacking faults extend the crack propagation path, thereby consuming energy and improving fracture toughness. Figure 5 The actual hardness of the sample is over 32 GPa. According to the optical photograph of the Vickers indentation, the fracture toughness of the sample can be calculated to be 5.0 MPa·m. 1 / 2 .
[0086] Example 6
[0087] 0.3 g of silicon carbide initial raw material (Innochem A08034) was heat treated in a tubular furnace, and the whole process was carried out in an argon environment. The heating rate was 20°C / min, the maximum temperature was 1500°C, and the holding time was 5 minutes. The treated powder was cold pressed into a column and placed in an assembly block, and then the assembly block was loaded into a T25 press and sintered at a pressure of 25 GPa and a temperature of 1700°C for 15 minutes. The heating rate was 50°C / min, and the cooling rate was 50°C / min. The sintered silicon carbide block is as follows Figure 1 (F), the central block is silicon carbide, and from the inside to the outside are silicon carbide, boron nitride crucible, and rhenium sheet. The final product is a single cubic phase silicon carbide, and its relative density, Vickers hardness, and fracture toughness are shown in Table 1. Its grain size, stacking fault density, and twin thickness measurements are shown in Table 2.
[0088] Table 1
[0089]
[0090] Table 2
[0091]
[0092] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
[0093] The optional materials of various components are listed in the description of the present invention, but those skilled in the art should understand that the above-mentioned list of component materials is not limiting and not exhaustive, and various components can be replaced by other equivalent materials not mentioned in the description of the present invention, while still achieving the purpose of the present invention. The specific embodiments mentioned in the description are also only for the purpose of explanation, and are not used as examples to limit the scope of the present invention.
[0094] In addition, the dosage range of each component of the present invention includes any combination of any lower limit and any upper limit mentioned in the specification, and also includes any range formed by combining the specific content of the component in each specific embodiment as the upper limit or lower limit: all these ranges are included in the scope of the present invention, but these combined ranges are not listed one by one in the specification just to save space. Each feature of the present invention listed in the specification can be combined with any other feature of the present invention, and such combination is also within the scope of the disclosure of the present invention: these combined ranges are not listed one by one in the specification just to save space.
Claims
1. A nanocrystalline silicon carbide bulk material, the average grain size of which is less than 100nm and the volume of the bulk material is greater than 1mm 3 , the relative density is greater than or equal to 98%, and the stacking fault density in the grain is 1.1*10 12 / cm 2 Up to 1.4*10 12 / cm 2 The thickness of twins in the grains is 3.2nm~4.5nm.
2. The nanocrystalline silicon carbide bulk material according to claim 1, characterized in that: The structural form of the block material is: only composed of a cubic phase (3C); or composed of a cubic phase (3C) and a hexagonal phase (2H).
3. The nanocrystalline silicon carbide bulk material according to claim 1, characterized in that: Vickers hardness value is equal to or higher than 30GPa, fracture toughness is equal to or higher than 4.5MPa·m 1 / 2 .
4. The nanocrystalline silicon carbide bulk material according to any one of claims 1 to 3, wherein the nanocrystalline silicon carbide bulk material is prepared by a method comprising the following steps: A) Pretreatment: Weigh mixed-phase silicon carbide nanopowder composed of cubic phase and hexagonal phase and perform heat treatment on it, wherein the grain size of the silicon carbide nanopowder is 10-100 nm, and the stacking fault density in the silicon carbide nanopowder grains is 1.4-2.5*10 12 / cm 2 , the average twin thickness is 1.2~2.8nm; B) Pre-pressing: pre-pressing the heat-treated raw material to obtain a pre-pressed green body; C) sintering: sintering the pre-pressed green body obtained in step B) at high temperature and high pressure; D) Discharging: Cooling and depressurizing the high-temperature and high-pressure sintering equipment in step C), then taking out the sintered silicon carbide block, and performing optional post-treatment to obtain a nanocrystalline silicon carbide block.
5. A method for preparing a nanocrystalline silicon carbide bulk material, characterized in that: A) Pretreatment: Weigh mixed-phase silicon carbide nanopowder composed of cubic phase and hexagonal phase and perform heat treatment on it, wherein the grain size of the silicon carbide nanopowder is 10-100 nm, and the stacking fault density in the silicon carbide nanopowder grains is 1.4-2.5*10 12 / cm 2 , the average twin thickness is 1.2~2.8nm; B) Pre-pressing: pre-pressing the heat-treated raw material to obtain a pre-pressed green body; C) sintering: sintering the pre-pressed green body obtained in step B) at high temperature and high pressure; D) Discharging: Cooling and depressurizing the high-temperature and high-pressure sintering equipment in step C), then taking out the sintered silicon carbide block, and performing optional post-treatment to obtain the nanocrystalline silicon carbide block.
6. The method for preparing nanocrystalline silicon carbide bulk material according to claim 5, characterized in that: The raw material used is only silicon carbide, the purity of the silicon carbide is ≥99%, and no sintering aid is added.
7. The method for preparing nanocrystalline silicon carbide bulk material according to claim 5, characterized in that: The heat treatment of the raw materials in step A) is carried out under vacuum or protective atmosphere.
8. The method for preparing nanocrystalline silicon carbide bulk material according to claim 5, characterized in that: In step C), the pre-pressed green body is sintered at a pressure of 8 GPa to 28 GPa and a temperature of 1000° C. to 2500° C. for 1 to 60 minutes.
9. The method for preparing nanocrystalline silicon carbide bulk material according to claim 5, characterized in that: In step A), the heating rate of the raw material heat treatment is 5-20°C / min, the maximum temperature is 500-1500°C, and the insulation time is 10-30min.
10. The method for preparing a nanocrystalline silicon carbide bulk material according to any one of claims 5 to 9, characterized in that: The structural form of the block material is: only composed of a cubic phase (3C); or composed of a cubic phase (3C) and a hexagonal phase (2H).
Citation Information
Patent Citations
Silicon carbide whisker ceramic with typical long particle morphology and rich in lamination faults and twin crystals and preparation method thereof
CN112645726A
Nanocrystalline silicon carbide superhard block and preparation method thereof
CN114315361A
Novel silicon carbide powder and calcined silicon carbide compact
JP1989294512A
SiC BODIES AND PROCESS FOR THE FABRICATION OF SiC BODIES
US20110028301A1
SiC VOLUMETRIC SHAPES AND METHODS OF FORMING BOULES
US20180290893A1